Blockchain for Vaccine Supply Chain: Challenges and Resilient Solution Strategies Facing Covid-19 - Dounia Saidi; Jamila El Alami; Mustapha Hlyal (Emerging Trends in Disease and Health Research Vol. 8, 2022)
The Covid-19 Pandemic crisis has disrupted current economic patterns and individuals habits. This disruptive event represents a great challenge for practioners and researchers in supply chain and logistics. The current health crisis has highlighted weaknesses in the end to end supply chain from purchase to delivery. Every part of the chain is under strain and exposed to high risks. However, in every crisis there is an opportunity. In terms of supply chain resilience, it is an opportunity to rethink the logistic schemes and the strategies to adopt. Everyone’s immunization is the key solution for an economic and social relaunch. Only a widely accessible vaccine could pave the way for a more complete recovery. However, this large scale operation is difficult to control and to ensure from end to end. Several risks are present: fraud, detour of vaccine, speculation, vaccine expiry, and control of cold chain. Participating in such a vaccine supply chain can protect lives and support a sustainable economic recovery. Through this chapter we aim to provide an overview about vaccine supply chain literature, key issues faced during Covid-19 health crisis, and network design and strategies adopted that might help for a social and economic recovery. Moreover, we aim to address main contraints of vaccine supply chain and how can Blockchain help to master flows along the value chain.